Anatomy of vegetative organs, inflorescence axis and pedicel in the Neoregelia bahiana complex (Bromeliaceae): taxonomic and ecological importance - Silva, Kleber Resende; Versieux, Leonardo M.; Oriani, Aline (Nordic journal of botany, 2018)
Delimitation of genera and species in Bromeliaceae is often problematic, for example in the Neoregelia bahiana complex which is distributed throughout the rocky fields of the Espinhaço Range, Brazil. Considering that the anatomical characterisation of different organs is potentially important for taxonomic and ecological interpretation of this complex, we analysed roots, stems (stolon), leaves, inflorescence axes (peduncle) and pedicels in individuals from different populations. In all the studied individuals, the roots are composed of velamen, a heterogeneous cortex, and a polyarch vascular cylinder with sclerenchymatous pith. The stolon features a parenchymatous cortex and collateral vascular bundles randomly distributed in the vascular cylinder. This organ may increase in diameter by the formation of new vascular bundles and a multi‐layered cork. The leaf blade has epidermal cells with U‐shaped thickened walls and peltate scales occur on the adaxial surface. The mesophyll consists of mechanical and water‐storage hypodermis and a heterogeneous chlorenchyma. The inflorescence axis and the pedicel have a parenchymatous cortex and vascular bundles randomly distributed in an aerenchyma. Some variable leaf characters, such as presence of air lacunae in the mesophyll, are related to the size of the individuals and were interpreted as phenotypic variations related mainly to sunlight incidence. In contrast, leaf characters such as lamina shape, distribution of the peltate scales, and number of cell layers forming the water‐storage hypodermis distinguish the populations of the Serra do Cabral and one population of the Diamantina (Minas Gerais) from the remaining studied populations, suggesting the existence of more than one taxon.